Application of QFD in Tanri Abeng University - Amanah Pasaribu, ST, MM (Management and Leadership Study Programme, 2019)
The university produces employee to work in industry. The challenge for the university isproducing the graduate who has a skill that industry need. The university needs to developquality of services. This research applies a Quality Function Development (QFD) method todevelop quality improvement of university. The finding of this reasearch shows that theuniversity has to develop curriculum, facility availability, lecturer capability andextracurricular activities.